Diffusion kurtosis imaging of brain white matter alteration in patients with coronary artery disease based on the TBSS method - Li, Tong; Qin, Rui; Li, Cuicui; Li, Lin; Wang, Ximing; Wang, Li (Frontiers in Aging Neuroscience, 2024)
Object: The aim of our study was to examine the alterations in microstructure in patients with coronary artery disease (CAD) and cognitive impairment (CI) using diffusion kurtosis imaging (DKI). Additionally, we aimed to investigate the potential correlation between DKI parameters and cognitive function. Materials & Methods: A total of 28 CAD patients and 30 healthy controls (HCs) were prospectively enrolled in our study. All participants underwent routine and diffusion sequences of head imaging. DKE software was utilized to generate various diffusion kurtosis imaging parameters (DKI), including kurtosis fractional anisotropy (KFA), mean kurtosis (MK), axial kurtosis (AK), radial kurtosis (RK), fractional anisotropy (FA), and mean diffusivity (MD). Nonparametric tests were conducted using tract-based spatial statistics (TBSS) to compare the parameter values between the two groups. The parameter values of the significantly different fiber tracts were extracted and correlated with the Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) scores. Results: Compared to the HC group, the CAD group showed significantly decreased values of FA, KFA, MK, and RK in multiple white matter fiber tracts (P < 0.01, TFCE corrected), while no significant differences were observed in other parameter values (P > 0.01, TFCE corrected). The FA values of the right posterior limb of the internal capsule (r = 0.610, P = 0.001) and the right cerebral peduncle (r = 0.622, P < 0.001) were positively correlated with MMSE scores. Additionally, a significant correlation between kurtosis and diffusion coefficient parameters (FA and KFA) was observed. Conclusions: CAD patients showed radial shrinkage and complexity of brain white matter microstructure. Whole-brain white matter analysis based on TBSS DKI can objectively reflect the characteristics of white matter damage in CAD patients, providing a basis for the auxiliary diagnosis of CAD with CI.